I’ll manage myself: the moderator effect of positive framing on the relationship between organisational politics and engagement - James, R. (Emerald Publishing Limited, 2021)
Purpose – This study aims to investigate the influence of organisational politics on work engagement and the moderator effect of positive framing on this relationship Design/methodology/approach – Data were collected from 241 public sector employees in Sri Lanka through a structured questionnaire and analysed with partial least square structural equation modelling (PLS_SEM). Findings – The results indicated that organisational politics negatively influenced employees’ work engagement, positive framing positively influenced engagement and weakened the negative relationship between politics and engagement. Practical implications – This study suggests that organisation and individuals must take the necessary steps to enhance work engagement. Organisations must be transparent in all activities to avoid employees’ negative perception. Also, organisations need to take steps to recruit employees with positive framing or develop this competency through training and development. Individuals also need to take necessary steps to frame the work environment positively to enhance their engagement in work. Originality/value – This study extends the literature by being the first to examine the positive framing as a moderator in the relationship between politics and engagement. This study found that positive framing as a resource reduced the harmful effect of organisational politics on engagement and suggested positive framing can be considered as a resource in the future investigation of the job demand–resource model.
Keywords: Management; HRM; Organizational politics; Engagement; Positive framing; Perception